Biodiversity in territorial relationship and resource: the case of camu-camu (Myrciaria dúbia; Myrtaceae) in the state of Amazonas-Brazil (Research, Society and Development, 2022)
This study analyzes the camu-camu (myrciaria dubia; myrtaceae) as an element of biodiversity and territorial resource mediated by biotechnology. Considering the commercial dimensions that the fruit assumes in the state of Amazonas, the objective is to analyze plant biodiversity as a territorial resource. The investigation was carried out from 2014 to 2018 and included a bibliographic survey on camu-camu, as well as interviews and fieldwork in the municipalities of Manaus and Silves, AM. The camu-camu, as an element of plant biodiversity, is natural, but its use and constitution, as a territorial resource and component of production chains, is socially produced with greater or lesser aggregation of biotechnology, techniques or capital investments. The objective of this work was to approach plant biodiversity as a resource, through the analysis of the camu-camu fruit (myrciaria dubia; myrtaceae), characteristic of the Amazon plant biodiversity. In order to understand the relationship between society and nature engendered in these dynamics, we present aspects of the natural space and the socioeconomic space of the fruit, predominantly considering the relationships in the biodiversity market. From this point of view, there is a territorial dialectic characteristic of this market, moved, simultaneously, by contributions and obstacles to horizontality and verticality.